2017
DOI: 10.2147/ijn.s130322
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis of dextran-coated iron oxide nanoclusters for real-time regional lymph node mapping

Abstract: The intraoperative precision cleaning of lymph nodes (LNs) is an essential component of treating neoplastic disease. To develop efficient probes for the targeted detection of LNs that could act as carriers for the specific diagnosis and treatment of metastatic LNs in the future, dextran-coated iron oxide nanoclusters (DIONs) were synthesized using a one-pot coprecipitation procedure. These modified DIONs have good water dispersibility, cytocompatibility, an optimum size, and a stable, dark brown color for LN i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 19 publications
(24 reference statements)
1
8
0
Order By: Relevance
“…In addition, Hauser et al found that synthetic methods, the amount of dextran can greatly affect the properties of the IONPs such as size, stability, crystallinity and magnetism [ 172 ]. Owing to its biosafety, bioactivity, biocompatibility, low cytotoxicity, dextran-coated IONPs are considered promising candidates for biomedical applications [ 173 ]. Unterweger et al developed a novel drug delivery system by coating IONPs with dextran and cisplatin hyaluronic acid.…”
Section: Surface Modification Of Magnetic Iron Oxide Nanoparticlesmentioning
confidence: 99%
“…In addition, Hauser et al found that synthetic methods, the amount of dextran can greatly affect the properties of the IONPs such as size, stability, crystallinity and magnetism [ 172 ]. Owing to its biosafety, bioactivity, biocompatibility, low cytotoxicity, dextran-coated IONPs are considered promising candidates for biomedical applications [ 173 ]. Unterweger et al developed a novel drug delivery system by coating IONPs with dextran and cisplatin hyaluronic acid.…”
Section: Surface Modification Of Magnetic Iron Oxide Nanoparticlesmentioning
confidence: 99%
“…Although WBC and PLT fluctuated among the three tests, no symptom of infection or anemia was found. Liver and kidney function and blood lipids were normal [ 34 ], as were GLU levels. Levels of immune-related factors and immune cells in the blood and spleen were also within the normal range.…”
Section: Discussionmentioning
confidence: 99%
“…At least three experiments were performed, and each was tested in triplicate. The experiment was repeated three times independently in the laboratory [ 25 ].…”
Section: Methodsmentioning
confidence: 99%